Enhancing Social-Emotional Skills in Junior High School Students through Project-Based Learning on Solar System Topics - Fazriah, Sarah Nur; Winarno, Nanang (Universitas Negeri Padang, 2025)
Early adolescence is a critical transitional period marked by significant physical, cognitive, and socio-emotional changes. During this crucial stage, developing social-emotional skills becomes essential to help adolescents adapt to the changes and challenges they face. This study aims to analyze the improvement of social-emotional skills among students by implementing a Project-Based Learning (PjBL) model on the Solar System. This study employed a pre-experimental design with a One-Group Pretest-Posttest Design. Data was collected using a social-emotional skills questionnaire. The study was conducted at a school in Bandung, Indonesia, with 35 seventh-grade students (14 males and 21 females) as participants. The results indicated a significant improvement in students' social-emotional skills, with a mean pre-test score of 74% and a mean post-test score of 77%. The N-Gain scores for Self-Awareness, Social-Awareness, Self-Control, Relationship Skills, and Responsible Decision-Making were 0.14, 0.12, 0.08, 0.04, and 0.05, respectively. Since all N-Gain scores were below 0.3, they can be interpreted as low. The findings suggest that the PjBL model can serve as an alternative for teachers to enhance students' social-emotional skills, particularly in science education.